Enzymatic activity of fungi isolated from crops - Żukiewicz-Sobczak, Wioletta A.; Cholewa, Grażyna; Sobczak, Paweł; Silny, Wojciech; Nadulski, Rafał; Wojtyła-Buciora, Paulina; Zagórski, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Aim: To detect and assess the activity of extracellular hydrolytic enzymes and to find differences in enzymograms between fungi isolated from wheat and rye samples and grown on Czapek-Dox Broth and Sabouraud Dextrose Broth enriched with cereal (wheat or rye). Isolated strains were also classified in the scale of biosafety levels (BSL). Material and methods: The study used 23 strains of fungi cultured from samples of wheat and rye (grain, grain dust obtained during threshing and soil) collected in the Lublin region (eastern Poland). API ZYM test (bioMérieux) was carried out according to the manufacturer’s instructions. Classification of BSL (Biosafety levels) was based on the current literature. Results : High enzymatic activity was found in strains cultured in media containing 1% of wheat grain ( Bipolaris holmi, Penicillium decumbens ) and with an addition of 1% of rye grain ( Cladosporium herbarum, Aspergillus versicolor, Alternaria alternata ). The total number of enzymes varied depending on the type of media, and in most cases it was higher in the culture where an addition of cereal grains was used. Conclusions : Isolated strains of fungi reveal differences in the profiles of the enzyme assay. It can be assumed that the substrate enriched in grains stimulate the higher activity of mold enzymes. Key words: enzymatic activity, mold fungi, zymogram, biohazards.